The Comparative Analysis of Consumer Protection Regulations in E-Commerce Transactions in Indonesia, Singapore and Malaysia - Najati, Fia Agustina; Mashdurohatun, Anis (Universitas Islam Sultan Agung, 2024)
Consumer protection for e-commerce transactions is a crucial thing that needs to be considered, starting from regulations, institutions, to implementation. It cannot be denied that consumer protection in Indonesia is not a priority for the government. This can be seen from outdated regulations, overlapping institutional authority, and ineffective implementation of law enforcement. Therefore, reform is needed by conducting comparative analysis between countries, for example with Singapore and Malaysia. The research method uses normative-comparative juridical research with a macro comparative approach. The research specifications used by the author are analytical descriptive and data sources through literature reviews using primary, secondary and tertiary methods. For data collection techniques, the author uses the library search technique. The research results showed that each regulation in each country has advantages and disadvantages, both in regulation and implementation. In Indonesia itself, regulations and their implementation still have many problems and need to be updated, especially in e-commerce (online) transactions. By updating these regulations, law enforcement can be strengthened and its implementation can be effective. Thus, preventing and reducing things that are detrimental to consumers and business actors.